MODIFIKASI HILL CIPHER DENGAN MENGGUNAKAN MATRIKS KUNCI ORTHOGONAL DAN TRANSPOSITION SUBSTITUTION LEFT RIGHT SHIFT (TSLRS) - Yuniardi Wahyu Nugraha; Thresye Thresye; Oni Soesanto (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2023)
Matrix is a collection of components arranged in rows and columns, concept of a matrix can be used in solving a problem related to cryptography. A mathematician named Lester Hill created a polyalphabetic cryptographic system called the Hill Cipher. Hill cipher is an algorithm that in its process uses a matrix with size (a × a) as the key matrix. The classic Hill Cipher has the disadvantage that the operation used is not complicated. In this study, the classic Hill Cipher will be modified by using an orthogonal matrix as the key matrix, as well as adding several other operations such as transposition, substitution, and bit shift. This study compares the performance of the traditional Hill Cipher and the modified Hill Cipher in terms of cryptographic techniques on data(text). This research was conducted by encrypting and decrypting the classic Hill Cipher and modified Hill Cipher using similar data (text). Furthermore, a simulation will be carried out using Matlab so that it can use data (text) with a larger size. The results obtained are Hill Cipher which has been modified using an asymmetric cryptographic system, that is in left-right shift process so that the matrix keys will be different when use for encryption and decryption. Because it uses a different key in the encryption and decryption process, thus increasing the level of difficulty in decoding the message.